The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s11743-006-5009-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel surfactants for ultralow interfacial tension in a wide range of surfactant concentration and temperature

Abstract: This work investigates the possibility of injecting dilute aqueous solutions of novel surfactants into the Yibal field (Sultanate of Oman). This was accomplished through an experimental protocol based on the following criteria: (i) compatibility of the surfactants with the high-saline reservoir water (~200 g/L); (ii) low interfacial tension (IFT) between crude oil and reservoir water (less than 10 -2 mN m -1 ); and (iii) maintaining the low IFT behavior during the entire surfactant flooding. Novel surfactants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 19 publications
4
79
0
Order By: Relevance
“…However, such surfactants are expensive. The use of a hydrophilic surfactant mixed with a relatively lipophilic surfactant or a new surfactant was also investigated [73][74][75]. However, studies on SP flooding only focused on the screening and evaluation of the polymer and surfactant and their interaction.…”
Section: Surfactant-polymermentioning
confidence: 99%
“…However, such surfactants are expensive. The use of a hydrophilic surfactant mixed with a relatively lipophilic surfactant or a new surfactant was also investigated [73][74][75]. However, studies on SP flooding only focused on the screening and evaluation of the polymer and surfactant and their interaction.…”
Section: Surfactant-polymermentioning
confidence: 99%
“…A more recent study reported that the price of biosurfactants ranges between US$ 2 and 3 per kg (Hazra et al 2011). It was reported that the reduction in interfacial tension (IFT) by the surfactants has to be ultra low, where the IFT values should be in the range of 10 3 mN/m, to enhance oil recovery by increasing the capillary number (Aoudia et al 2006;Curbelo et al 2007;Zhu et al 2009;Iglauer et al 2010;Lu et al 2014a, c, d). Although the minimum IFT value obtained by the biosurfactant in this study is not ultra low, other recovery mechanisms are expected to take place.…”
Section: Introductionmentioning
confidence: 99%
“…However, such surfactants are expensive. The use of a hydrophilic surfactant mixed with a relatively lipophilic surfactant or a new surfactant was also investigated (Rosen et al 2005;Aoudia et al 2006;Cui et al 2012). However, studies on SP flooding only focused on the screening and evaluation of the polymer and surfactant and their interaction.…”
mentioning
confidence: 99%